Difference of high-light stress sensitivity in the two firs, Abies mariesii and Abies veitchii, in early spring - Yamazaki, Jun-ya; Suzuki, Ayumi; Okuyama, Yuki; Maruta,Emiko; Kamimura, Yasumaro (National Institute of Polar Research, 2003)
P(論文) Abies veitchii and Abies mariesii are dominant species at the tree-line in Central Japan. Recently, we observed needle death, probably due to photodamage of the photosynthetic apparatus at the tree-limit during March-April. A. veitchii survives winter without any needle death due to photodamage at the tree-line. However, there is no conspicuous damage between the two species because this phenomenon is only observed at the tree-limit. In this study, we examined the difference in winter down-regulation of PS II between A. veitchii and A. mariesii and observed the following results: In March, (1) Fv/Fm of both species was about 0.1, showing the photochemical efficiency being severely inhibited. (2) The de-epoxidation state, expressed as [(A+Z)/(V+A+Z)], was about 0.35 for both species. (3) Chlorophyll (Chl) content of A. veitchii was much less than that of A. mariesii and Pchlide was found only in A. veitchii. In April, (1) Fv/Fm increased and [(A+Z)/(V+A+Z)] decreased for both species. (2) Chl content of A. veitchii increased by four-fold while Pchlide nearly dissappeared. These results indicate the following: During cold periods, most of Chl of A. veitchii may have been converted to Pchlide which is easily re-converted to Chl in spring, an intermediate of Chl biosynthesis. Winter conversion from Chl to Pchlide in A. veitchii may provide effective protection from photodamage of the photosynthetic apparatus. Furthermore, this may explain the higher ability of A. veitchii to prevent photodamage compared to A. mariesii. departmental bulletin paper